The Effect of Ownership Structures and Earnings Management on Dividend Policy in Indonesia Mining Industry from 2015 to 2019 - Arifani, Yusnia Talitha AGnes; Nainggolan, Yunieta Anny (Journal of Business and Management, 2020)
Abstract. Indonesia Mining sector has an important role in contributing to the countrys' revenue, so its existence on the Indonesia stock market is often the target of many investors. However, its fluctuating commodity prices have an impact on the firms'profit and earnings that lead firms to do earnings management and raise an agency conflict since earnings used as dividends predictor. The presence of ownership structures defined by institutional and managerial ownership is one of factors that might influences dividend policy and hopefully can align that situation. By using two measurements such as dividend payout ratio and cash dividend, this research tries to analyze the situation impact on dividend policy with quantitative method. The sample is obtained from Mining firms listed on Indonesia Stock Exchange within 2015 to 2019. The panel data regression is performed and result that institutional ownership and earnings management have no significance effect on dividend policy. Meanwhile, it is found managerial ownership has a positive significant effect on dividend policy in Indonesia Mining industry. The result can be supported by agency theory as the manager shareholders can help to cope with agency conflict and the bird in hand theory explained for the investor who prefer higher dividend since higher value in managerial ownership result in higher dividend.Keywords: Dividend Policy, Institutional Ownership, Managerial Ownership, Earnings Management.